Os perigos do individualismo: um ensaio hermenêutico sobre Alexis de Tocqueville e Hannah Arendt - Gonçalves, Vittória Catharina Avelino (Brasil, 2025)
The theoretical approaches between Hannah Arendt and Alexis de Tocqueville are undeniable and need to be revisited due to the need to maintain what we think is Democracy. The concern of this present research is to clarify the path on which we follow as a society, precisely a democratic society, and the dangers we encounter and face. Hannah Arendt, to prevent the emergence of a totalitarian state, and Alexis de Tocqueville, to demonstrate the process of equalization in which democratic societies developed their vices, even identify individualism as the greatest danger to democracy. The center of the study, then, is this conceptual convergence that opens up a range of analytical possibilities and possible studies that incorporate these authors, indicating the dangers inherent to democracy, highlighting individualism as the catalyst for such disastrous consequences.